Evaluation of Renal Osteodystrophy and Serum Bone‐Related Biomarkers in a Peritoneal Dialysis Population. (6th July 2022) - Pereira, Luciano; Magalhães, Juliana; Mendonça, Luís; Neto, Ricardo; Santos, Janete; Carvalho, Catarina G; Oliveira, Ana; Beco, Ana; Frazão, João
ABSTRACT: The spectrum of renal osteodystrophy (ROD) in peritoneal dialysis (PD) patients remains to be clarified. Ideal intact parathormone (iPTH) levels range is still not defined. The role of sclerostin, dickkopf‐related protein 1, osteoprotegerin, and receptor activator for nuclear factor κB ligand for the diagnosis of ROD needs to be elucidated. In this cross‐sectional study, tetracycline double‐labeled bone biopsy was performed in 49 patients with histomorphometric analysis according Kidney Disease Improving Global Outcomes (KDIGO) guidelines. All patients were treated with biocompatible PD solutions, with calcium concentration of 1.25 mmol/L. Adynamic bone was the most frequent diagnosed pattern (42.9%) followed by hyperparathyroid‐related bone disease (28.6%). Twenty‐two percent of patients had normal bone. In patients with iPTH within the KDIGO recommended range for dialysis patients, adynamic bone was found in 59% of cases. Median (range) iPTH in patients with adynamic bone was 312 (60–631) pg/mL. Median (range) levels of sclerostin varied from 1511.64 (458.84–6387.70) pg/mL in patients with hyperparathyroid bone disease to 2433.1 (1049.59–11354.52) pg/mL in patients with adynamic bone. Sclerostin/iPTH ratio was the best marker of low turnover disease but iPTH performed best in the diagnosis of high turnover disease. Calcium mass transfer was positive in patients with low bone volume. Adynamic bone is the most frequent ROD pattern in contemporary PD. Our results suggest the need to review the iPTH target range for this population. The sclerostin/iPTH ratio showed improved performance compared to iPTH for the diagnosis of low turnover bone. © 2022 American Society for Bone and Mineral Research (ASBMR).